"Buy-in": An Undervalued Factor. (May 2022) - Kilian, Jon
Abstract : Buy-in is a frequently disregarded aspect of health professions that is vital to pursue with each client to fully optimize outcomes. The Health Belief Model provides perceived aspects of behavioral change that, when used in conjunction with the patient-centered biopsychosocial approach along with other behavioral change theories, can assist in identifying and overcoming potential obstacles for the client. To optimize outcomes is to strive for buy-in through each interaction. Apply It!: Each client a health professional comes across fits into the Health Belief Model and Biopsychosocial model in their own specific way at that period in time; it is vital to identify and address potential barriers as soon as possible to optimize outcomes. Educating your client on the "why" can address each of the six constructs of the Health Belief Model and, therefore, may be the best strategy to begin to elicit behavioral change. The goal from the beginning of each client interaction should be to build rapport; this will be the basis on which any strategy used for behavioral change depends. To do so, connect, engage, and follow-through. Building culture is a long-term goal of the overall workplace; be exemplary, intentional, and consistent in your behaviors.